Analisis Butir Variabel Kepercayaan Pada Organisasi Menggunakan Rasch Model - Rais Hidayat (Jurnal Manajemen, 2019)
Organization trust is "lubricant" in the organization. This research aims to obtain instrument items that can be used in the organization trust research, to obtain the items that are difficult to approve and vice versa, and to obtain the perceptions of respondents on each instrument item. This research method uses to test the instrument items. The research was conducted at Private Universities in Bogor, West Java, Indonesia with a sample of 133 lecturers who had a National Lecturer Registration Number (NIDN) and had a functional position. Research findings include: as many as 28 out of 33 items can be used to examine organizations trust, and fair rewards, effective communication and involvement of lecturers in decision making are things that must be corrected at private universities. It is hoped that these findings will be a material for discussion to increase organizational trust.